Quality indicators and biological value for eggs ozonation - P A Popov (RUDN Journal of Agronomy and Animal Industries, 2012)
In this study, qualitative indicators of the eggs in their ozonization with the definition of the amino acid composition, fatty acid composition and determination of their biological value.